Protein degradation in Escherichia coli: the lon gene controls the stability of sulA protein. - Mizusawa, S (1983)
Escherichia coli lon mutants are defective in the ATP-dependent proteolysis of abnormal proteins. The mutants are also sensitive to ultraviolet light (UV) in that septation is inhibited after exposure to UV. sulA mutations, isolated as suppressors of UV sensitivity unlinked to lon, do not affect proteolysis but allow septation to occur after DNA damage. We have confirmed the hypothesis that the product of the sulA gene is degraded by lon proteolysis. If sulA (the product of sulA) is a UV-inducible division inhibitor, as suggested by a variety of experiments, lon (the product of lon) may regulate cell division by regulating the half-life of sulA. We cloned the sulA gene in a bacteriophage lambda vector from a plasmid carrying the ompA region of E. coli. An 18-kilodalton polypeptide was identified as the product of the sulA gene. Pulse-chase labeling demonstrated that the half-life of the sulA protein is 1.2 min in lon+ cells and 19 min in lon- cells. This work demonstrates that lon proteolysis affects the stability of a native E. coli protein.